The Effect of Emotional Intelligence on Resilience in Female Employees at PT “X” East Jakarta - Maria Kristiana, Cindy; Silvia Ramadhani, Nurulita; Muamana Tanzilla Hastomo, Nurhidayah (International Journal of Social Science, Education, Communication and Economics, 2024)
Workload is a responsibility that each worker has to take on, but if the workload has an excessive quantity in many ways, it will certainly have a negative impact on the workers concerned. It is caused by all forms of workload that can provide its own pressure for female employees with all the demands that exist, such as one of which is that female employees must still be able to perform stable or good performance in accordance with existing standards. In this situation, an ability called resilience is needed. Resilience will allow a person to keep standing upright in the face of existing problems and actively seek solutions to the problems being faced. Good resilience can greatly help female employees to be able to optimize their work, even in difficult times so that it has an impact on their health both physically and mentally, and affects the success achieved in interacting with their environment and remaining productive in carrying out their responsibilities to the fullest. Female employees who have resilience are certainly supported by a factor such as emotional intelligence that can help female employees increasingly have an awareness of the importance of resilience when facing existing difficulties. This study aims to determine the effect of emotional intelligence on resilience owned by female employees, especially those at PT "X" East Jakarta. This study involved 40 employees at PT "X" East Jakarta. The measuring instruments used in this study are resilience scale and emotional intelligence scale. The results of simple regression analysis show that emotional intelligence has a positive influence on resilience owned by employees at PT "X" East Jakarta. Emotional intelligence affects a person's level of resilience. The implication of this research is that can provide information to employees at PT "X" East Jakarta and or general readers who have the same condition to be more aware of the importance of having resilience and knowing the emotional intelligence factors that exist to still be able to help further improve resilience when in a difficult situation or condition such as pressure or a lot of workload.